The inhibitory effect of some medical plants on the growth of some bacterial isolates from respiratory infections: Al-Jebouri, A.J Abbas, M.S. Eaal, N.M. - A.J, Al-Jebouri (The Iraqi Journal of Veterinary Medicine, 2010)
This study was carried out to evaluate seven types of herbs being: black pepper seeds (Piper nigrum), celery seeds (Apium graveolens), cubeb seeds (Piper cubeba), camphor seeds (Cinnamomuum camphora), myrrh (Commiphora mol mol), fenugreek seeds (Trigonella foenum- graecum) and seeds of Lepidium sativum. The antibacterial activity of alcoholic extracts of these plants was performed on gram- positive and gram- negative bacteria isolated from human respiratory tract infections including : S. aureus ,S. pneumoniae, M. antarcticus, Corynebacterium spp. and coagulase- negative Staphylococci (CNS). Gram –negative bacteria included: K. oxytoca, K. pneumoniae and N. meningitidis, P. aeruginosa and E. coli. We studied the bacterial sensitivity to 10 antibiotics: Tobramycin (TOB), Ceftazidime (CAZ), Vancomycin (VA), Ampicillin (AM), Ofloxacin (OFX), Cloxacillin (CX), Cefalothin (KF), Erythromycin (E), Oxytetracycline (T), Amoxicillin/Clavulanic acid (CTX). Cubeba essential oil was superior in inhibiting all the examined bacteria compared with other plants. K. oxytoca was most sensitive to Lepidium sativum seeds extract followed by myrrh and fenugreek, while K. pneumoniae was most sensitive to cubeba and camphora. Cubeba followed by myrrh pi spp. was resistant to 5 antibiotics and sensitive to 4 which were: TOB, VA, OFX and KF.